Implementasi Literasi Budaya dan Kewarganegaraan Sebagai Solusi Disinformasi Pada Masyarakat Indonesia - Deby Sabina; Dinie Anggraeni Dewi; Rizky Saeful Hayat (Jurnal Pendidikan Indonesia (JOUPI), 2023)
Disinformation is the result of the spread of fake news that is spread online in cyberspace, so that many people easily accept the information they receive without having to look for the original source of the information. Finally, people do not have the analytical skills needed to use information. Therefore, the aim of this research is to provide an overview of the disinformation that exists in society and to clarify how civic and cultural literacy can be used to address disinformation. The method used is a literature study method with a qualitative approach. The type of data used in this research is data obtained from literature studies. The results of this research found that the application of cultural and civic literacy is very necessary to prevent and overcome disinformation.